Lizards possess the most complete tetrapod Hox gene repertoire despite pervasive structural changes in Hox clusters. Issue 4 (10th July 2019) - Feiner, Nathalie; Wood, Natalie J.
Abstract: Hox genes are a remarkable example of conservation in animal development and their nested expression along the head‐to‐tail axis orchestrates embryonic patterning. Early in vertebrate history, two duplications led to the emergence of four Hox clusters (A‐D) and redundancy within paralog groups has been partially accommodated with gene losses. Here we conduct an inventory of squamate Hox genes using the genomes of 10 lizard and 7 snake species. Although the HoxC1 gene has been hypothesized to be lost in the amniote ancestor, we reveal that it is retained in lizards. In contrast, all snakes lack functional HoxC1 and ‐D12 genes. Varying levels of degradation suggest differences in the process of gene loss between the two genes. The vertebrate HoxC1 gene is prone to gene loss and its functional domains are more variable than those of other Hox1 genes. We describe for the first time the HoxC1 expression patterns in tetrapods. HoxC1 is broadly expressed during development in the diencephalon, the neural tube, dorsal root ganglia, and limb buds in two lizard species. Our study emphasizes the value of revisiting Hox gene repertoires by densely sampling taxonomic groups and its feasibility owing to growing sequence resources in evaluating gene repertoires across taxa. Abstract : The HoxC1 gene, assumed to be lost in the amniote ancestor, is retained in lizards and expressed in the early embryo. HIGHLIGHTS: Exploration of the genomes of 17 lizard and snake species revealed the presence of a Hox gene, HoxC1, that has been thought to be lost in the amniote ancestor. This finding sheds new light on the evolution of Hox gene repertoires.